2018
DOI: 10.1002/ece3.4524
|View full text |Cite
|
Sign up to set email alerts
|

Size‐dependent movement explains why bigger is better in fragmented landscapes

Abstract: Body size is a fundamental trait known to allometrically scale with metabolic rate and therefore a key determinant of individual development, life history, and consequently fitness. In spatially structured environments, movement is an equally important driver of fitness. Because movement is tightly coupled with body size, we expect habitat fragmentation to induce a strong selection pressure on size variation across and within species. Changes in body size distributions are then, in turn, expected to alter food… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
(121 reference statements)
1
22
0
Order By: Relevance
“…In flying arthropods, wing loading (ratio of body mass to wing area) can scale positively but also negatively with body mass depending on the species (Boiteau & Colpitts, 2001;Darveau, Hochacka, Welch, Roubik, & Suarez, 2005;Gilchrist & Huey, 2004), implying that larger individuals are not necessarily better fliers. Other differences in ecology and behaviour might be related to body size within a species (Hillaert, Hovestadt, Vandegehuchte, & Bonte, 2018). For instance, in a study on the near-threatened beetle Osmoderma eremita (Nieto & Alexander, 2010), it was observed that radiotagged beetles survived better than beetles marked for classic capture-mark-recapture analysis (Le Gouar, Dubois, Vignon, Brustel, & Vernon, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In flying arthropods, wing loading (ratio of body mass to wing area) can scale positively but also negatively with body mass depending on the species (Boiteau & Colpitts, 2001;Darveau, Hochacka, Welch, Roubik, & Suarez, 2005;Gilchrist & Huey, 2004), implying that larger individuals are not necessarily better fliers. Other differences in ecology and behaviour might be related to body size within a species (Hillaert, Hovestadt, Vandegehuchte, & Bonte, 2018). For instance, in a study on the near-threatened beetle Osmoderma eremita (Nieto & Alexander, 2010), it was observed that radiotagged beetles survived better than beetles marked for classic capture-mark-recapture analysis (Le Gouar, Dubois, Vignon, Brustel, & Vernon, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By constraining reproduction, herbivore population growth is strongly reduced, thereby promoting predator mobility even when P is high. This mechanism is confirmed by the observation that lowering resource growth speed within the resource‐herbivore model also resulted in selection of larger herbivores (Hillaert, Hovestadt, et al, ). Under low P and low herbivore reproductive values, the largest predators can no longer persist due to food limitation and selection turns towards smaller average predator sizes.…”
Section: Discussionmentioning
confidence: 58%
“…Theoretical studies have demonstrated that large individuals within species’ populations or large species within communities can be selected with increasing levels of isolation and habitat fragmentation due to their high ability to cross unsuitable matrix, that is their gap‐crossing ability (Etienne & Olff, ; Hillaert, Hovestadt, Vandegehuchte & Bonte, ). These dynamics are especially prominent in systems where resources are static and when consumers move in a fully informed manner (Hillaert, Vandegehuchte, Hovestadt & Bonte, ).…”
Section: Introductionmentioning
confidence: 99%
“…As these physiological changes are anticipated to be correlated with demographic traits and behaviours, hence forming behavioural syndromes [26,81,170] they can eventually impact equilibrium population sizes and their fluctuations [171], as mediated by costs during movement and changes in local growth rates (e.g., [172,173]). Such feedbacks can even be lagged if physiological responses are mediated through maternal effects, as for instance the case by induced hormonal effects [33].…”
Section: Closing the Loopmentioning
confidence: 99%
“…The physiological control of movement should therefore be treated as a reaction norm, and as for models including feedbacks between evolution and ecology [197], we expect a realistic but simplified consideration of feedbacks between environmental cues, resources and physiological processes to improve the predictive power of the available models. The integration of simple allometric and metabolic rules offers in this respect promising avenues [171,[198][199][200][201], as do dynamic energy budget models [202][203][204]. It is less obvious to which degree any hormonal feedbacks need to be integrated.…”
Section: A Critical End-reflectionmentioning
confidence: 99%